Implementation of Video Media to Improve Development of Early Religious and Moral Values of Children - Dewi Mike Oktavia; Junaisih Dewi Madya (Jurnal Pendidikan Indonesia, 2021)
This study aims to prove that there is an influence of the use of video media on the development of religious and moral values by introducing polite behavior. This research uses a quantitative quasi-experimental design with a pretest-posttest controlled group design model. Learning in the control group using a conventional model teacher-centered media storybook while the experimental group using the medium of video. This research was conducted in kindergarten TRI DHARMA sub-district Sukapura districts Probolinggo in group A with research subjects 20 children to group control and 20 children to experiment. From the results of this study indicate that the influence of experimental class children who use video media has an average higher when compared to the control class that uses conventional models that are centered on the teacher with the storybook media. The average score of the experimental class is 82.25 and the average number of the control class is 75.5. Based on the analysis of data that has been done that t arithmetic > t table, which is 2.163 > 2.08387. Thus it can be concluded that video media influences the development of religious and moral values of early childhood.